2005
DOI: 10.2134/agronj2004.0071
|View full text |Cite
|
Sign up to set email alerts
|

Legume Green Fallow Effect on Soil Water Content at Wheat Planting and Wheat Yield

Abstract: Growing a legume cover crop in place of fallow in a winter wheat (Triticum aestivum L.)–fallow system can provide protection against erosion while adding N to the soil. However, water use by legumes may reduce subsequent wheat yield. This study was conducted to quantify the effect of varying legume termination dates on available soil water content at wheat planting and subsequent wheat yield in the central Great Plains. Four legumes [Austrian winter pea, Pisum sativum L. subsp. sativum var. arvense (L.) Poir.;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
96
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(109 citation statements)
references
References 16 publications
8
96
1
4
Order By: Relevance
“…They avoid nutrient losses and soil erosion, provide additional organic input to the soil and improve its physical, chemical and biological quality (MacRae and Mehuys 1985;Meyer et al 1999;Schutter and Dick 2002;Vidal and López 2005;Liu et al 2005). Introduction of an additional crop, however, was considered to reduce water storage compared to an otherwise bare soil, resulting in higher depletion at planting of the subsequent main crop (Mitchell et al 1999;Nielsen and Vigil 2005;Islam et al 2006). On the contrary, Bodner et al (2007) reported only low differences in evapotranspiration between a cover cropped and a bare soil under semi-arid, supply-driven conditions in East Austria.…”
Section: Initial Depletionmentioning
confidence: 99%
See 1 more Smart Citation
“…They avoid nutrient losses and soil erosion, provide additional organic input to the soil and improve its physical, chemical and biological quality (MacRae and Mehuys 1985;Meyer et al 1999;Schutter and Dick 2002;Vidal and López 2005;Liu et al 2005). Introduction of an additional crop, however, was considered to reduce water storage compared to an otherwise bare soil, resulting in higher depletion at planting of the subsequent main crop (Mitchell et al 1999;Nielsen and Vigil 2005;Islam et al 2006). On the contrary, Bodner et al (2007) reported only low differences in evapotranspiration between a cover cropped and a bare soil under semi-arid, supply-driven conditions in East Austria.…”
Section: Initial Depletionmentioning
confidence: 99%
“…These different findings are mainly related to the duration and climatic conditions during cover crop growth. Those studies reporting significant soil water depletion were conducted in locations with higher temperature during cover crop growth (Central Great Plains; Nielsen and Vigil 2005) and/or predominant winter rainfalls (California; Mitchell et al 1999;Islam et al 2006). On the contrary, in the semi-arid continental climates of Central and Eastern Europe, the main growing period of cover crops is autumn until crops are terminated by frost before winter.…”
Section: Initial Depletionmentioning
confidence: 99%
“…Nielsen and Vigil (2005) indicated that soil moisture was an important factor in determining the residual benefits to cereals grown in rotation with green manure legumes in North America. Short duration, determinate legumes may result in more residual soil water for subsequent crops whereas long duration and/or indeterminate legumes may remove more water than cereal crops.…”
mentioning
confidence: 99%
“…Wheat yield in the wheat-corn-millet system averaged 52% (1530 kg ha 21 ) less than in the wheatcorn-fallow system. Wheat yield has been reported to be strongly correlated with available soil water at wheat planting (Nielsen et al, 1999;Nielsen et al, 2002;Nielsen and Vigil, 2005), with the response ranging from 39.7 to 282.9 kg ha 21 cm…”
mentioning
confidence: 99%